Dampak Program Keluarga Harapan Terhadap Kesejahteraan Keluarga Penerima Manfaat di Kecamatan Gambut Kabupaten Banjar - Muhammad Rizaldy Nugraha (Pusat Pendidikan, Pelatihan, dan Pengembangan Profesi Kesejahteraan Sosial (Pusdiklatbangprof Kesos), Kementerian Sosial RI, 2023)
Muhammad Rizaldy Nugraha (2023), the impact of the Family Hope Program on the welfare of Beneficiary Families in Gambut District, Banjar Regency. This study aims (1) to find out the implementation of the Family Hope Program for the welfare of Beneficiary Families (KPM) in Gambut District, Banjar Regency. (2) Knowing the impact of the implementation of the Family Hope Program on the welfare of Beneficiary Families (KPM) in Gambut District, Banjar Regency. Respondents in this study were 85 respondents from Gambut District, Banjar Regency, and this study used a descriptive qualitative method of data collection techniques by interviewing, observation, and documentation. Data analysis by analyzing the impact on respondents and SWOT analysis. The results of this study indicate that the impact of the Family Hope Program (PKH) has a positive impact on the welfare of Beneficiary Families (KPM), it can be seen from their improved socioeconomic conditions, good education levels of their children, good nutritional health status of mothers and children families and adequate, and access to adequate health and education. Keywords: Impact, Welfare, Family Hope Program, Beneficiary Families